Penerapan Nilai-nilai Tasawuf dalam Pembinaan Akhlak Santri pada Pondok Pesantren Miftahul Huda Gading Malang - Nur Yasin; Sutiah Sutiah (Madrasah Tsanawiyah DDI Cilellang, 2020)
This study aims to find out (1) the program of implementing Sufism values in the moral development of santri at Miftahul Huda Gading Malang Islamic Boarding School; (2) the process of implementing Sufism values in the moral development of santri at Miftahul Huda Gading Malang Islamic Boarding School; and (3) the success of Sufism values in the moral development of santri at Miftahul Huda Gading Malang Islamic Boarding School. The type of study is a case study with the qualitative method. The data collection uses the method of observation, interviews, and documentation. As for the data analysis using a case study qualitative analysis. The results show that the implementing Sufism values in the moral development of santri Miftahul Huda Islamic Boarding School have three programs: (1) Diniyah formal namely Madrasah Matholiul Huda with the Sufism curriculum that obligatory follow for every santri; (2) Nonformal learning namely cottage learning in outside the formal time which took place in the mosque, hall and in the house of the caregiver; (3) Toriqoh namely toriqoh qodiriyah wa naqsabandiyah followed only by santri who fulfilled the requirements. While the process of implementing the values of Sufism in the moral development of santri at Miftahul Huda Islamic Boarding School (a) through habituation of dhikr to fard prayer, (b) uswatun hasanah or caregiver status, (c) tasawuf through education, and (d) toriqoh. The success implementing Sufism values in the moral development of santri Miftahul Huda Islamic Boarding School is characterized by changes in santri’s behavior and attitudes or can be judged by the evaluation of Bloom, namely cognitive, affective, and psychomotor.